Favorite E-Learning Media in Pandemic Covid-19 Era - Geminastiti Sakkir; Syarifuddin Dollah; Jamaluddin Ahmad (Jurnal Studi Guru dan Pembelajaran, 2020)
It has been almost a year since we experienced the Covi-19 pandemic, which made us carry out learning activities from home. In filling that period, the researchers intends to conduct research that can add references to the learning process in this challenging time. The purpose of this research is to know students’ perception on the use of E- learning Media in Covid-19 pandemic era; the lecturers’ favorite e-learning media in Covid- 19 pandemic era; the students’ favorite e-learning media in Covid- 19 pandemic era and the factors affects the use of E- learning in the classroom. This study was a descriptive and use a mixed method consisted of quantitative and qualitative data. The sample of this study (n= 20) is the sixth semester undergraduate students from English Education Department of 2019/2020 academic year, Universitas Muhammadiyah Sidenreng Rappang, Indonesia. The results of this study showed that there are many E- learning media that the lecturers used in delivering the materials. The use of that media in learning process is less interested to the students. It was proved by the results of students’ perception. These scores are categorized as disagree or negative scores of perceptions if they are confirmed by using a Likert Scale. There are no students who strongly agree with the current e-learning process, there are only 3 students who agree, 11 students say they are moderate (55%), 5 students disagree and 1 student strongly disagree. However, the use of e-learning media in the current learning process is an absolute necessity. Favorite learning media that are often used by lecturers in teaching, such as Zoom, WhatsApp and LMS, while students prefer to be taught with WhatsApp, Zoom, Google Classroom, LMS, and Quizziz.